2018
DOI: 10.1088/2399-6528/aab51b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of entanglement and quantum states transitions in spin-qutrit systems under classical dephasing and the relevance of the initial state

Abstract: We provide a detailed analysis of the time-evolutions of free and bound entangled states in a twoqutrit system under the effects of local/non-local classical dephasing noises. Namely the Ornstein-Uhlenbeck (OU) and the static noise are considered. The importance of the initial state is also analyzed by considering two completely different initially entangled states and their respective locally equivalent states by means of local unitary operation (LUO). The qutrits isotropic and bound entangled states are stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…In many quantum mechanical protocols, the OU method is a static Gaussian-Markov operation with OU noise, and it has been identified as one of the numerous and primary causes of information, coherence, and quantum correlation losses [28]. OU noise has been extensively studied in the case of single qutrit, two-qubit, three qubits, and hybrid qubit-qutrit states and we find that in each case, the degree and behavior of losses are different [26,37,38]. Currently, the OU noise is applied to the dynamical map of the two-qubit mixed Werner state, which is created in the state ρ o .…”
Section: Suggested Model and Dynamicsmentioning
confidence: 88%
See 1 more Smart Citation
“…In many quantum mechanical protocols, the OU method is a static Gaussian-Markov operation with OU noise, and it has been identified as one of the numerous and primary causes of information, coherence, and quantum correlation losses [28]. OU noise has been extensively studied in the case of single qutrit, two-qubit, three qubits, and hybrid qubit-qutrit states and we find that in each case, the degree and behavior of losses are different [26,37,38]. Currently, the OU noise is applied to the dynamical map of the two-qubit mixed Werner state, which is created in the state ρ o .…”
Section: Suggested Model and Dynamicsmentioning
confidence: 88%
“…L(τ ), R(τ ), and U (τ ) all have a monotonic qualitative dynamical behaviour that is compatible with C(τ ). Different types of quantum systems remained entangled depending on the type of system-environment interaction given in [15,28,[36][37][38], but the current bipartite Werner state becomes completely disentangled. 11) for independent qubit-noise configuration when p = 1.…”
Section: Entropic Uncertainty and Concurrence Against Noise Parameter...mentioning
confidence: 99%
“…Note that  is non-negative and non-increasing under classical mixing. [47] For a 2 ⊗ d (qubit-qudit) quantum system, the LQU can be summarized as a compact formula [48] (𝜌) = 1 − 𝜆 max ( AB ), (27) in which 𝜆 max stands for the largest eigenvalue of the 3 × 3 matrix  AB with the following elements…”
Section: Local Quantum Uncertaintymentioning
confidence: 99%
“…[17][18][19] Hence, many analytical tools, simulation techniques and several other methods for calculating and quantifying quantum correlations have been investigated to explore the separability of bipartite quantum systems. [20,21] Importantly, recent works shed light on studying quantum correlations for qubit-qutrit and qutritqutrit states, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] which creates a fascinating future in quantum technologies. [39] Due to the possibility of maximum control of the associated Hilbert space, hybrid qubit-qudit systems have become increasingly important in the field of quantum information.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of qutrits (and qudits in general) in quantum simulations of physics problems are also being explored [61,62]. It was suggested that entangled qutrits are less affected by noise than the entangled qubits [63,64]. It might be interesting to see how it affects the coherent forward scattering in neutrinos.…”
Section: Introductionmentioning
confidence: 99%